Efficacy and safety of obinutuzumab for the first-line treatment of follicular lymphoma: a subgroup analysis of Chinese patients enrolled in the phase III GALLIUM study. Issue 4 (20th February 2022) - Hong, Xiaonan; Song, Yuqin; Shi, Yuankai; Zhang, Qingyuan; Guo, Wei; Wu, Gang; Li, Junmin; Feng, Jifeng; Kinkolykh, Anastasiia; Knapp, Andrea; Lin, Tongyu
Abstract: Backgrounds: GALLIUM is a global phase III study that demonstrated significant improvements in progression-free survival (PFS) for obinutuzumab plus chemotherapy (G-chemo) vs . rituximab plus chemotherapy (R-chemo) in previously untreated patients with follicular lymphoma (FL). This study aimed to report the results of a subgroup of patients in China. Methods: Patients were randomized to G-chemo or R-chemo. Responders received maintenance therapy for 2 years or until disease progression. The primary endpoint was investigator (INV)-assessed PFS. Secondary endpoints included the overall response rate (ORR) and complete response rate (CRR) at the end of induction chemotherapy, overall survival (OS), and safety. Results: Overall, 58 patients with FL were randomized to the G-chemo ( n = 25) and R-chemo arms ( n = 33). The INV-assessed PFS rate at 3 years was 81.8% in the G-chemo arm, vs . 70.2% in the R-chemo arm (hazard ratio 0.35; 95% confidence interval: 0.09–1.34; P = 0.1120). The INV-assessed CRRs (without positron emission tomography [PET]) in these arms were 24.0% and 21.2%, respectively, whereas the ORRs were 80.0% and 90.9%, respectively. INV-assessed CRR-PET was 52.6% in the G-chemo, vs . 60.9% in the R-chemo. Median OS was not reached in either arm. Grade 3 to 5 adverse events were more frequent in the R-chemo arm (97.0% vs . 88.0%). Conclusions: The results of this subgroup analysis were consistent with those of the global population, and they suggest that G-chemo has a positive benefit–risk profile in patients from China with FL. Trial registration: ClinicalTrials.gov, No. NCT01332968.